Vesiculobullous diseases, connective tissue and rheumatological disorders - Mohammed Shanshal (Our Dermatology Online, 2022)
This section reviews the emergency presentations of autoimmune blistering diseases, connective tissue and rheumatological disorders as well as common pitfalls associated with their diagnosis and management